Managing a Canadian healthcare strategy - Carson, A. Scott; Nossal, Kim Richard (Queen's policy studies., 2016)
"Canada's fragmented healthcare system is one of the most expensive among the OECD countries, yet the quality of its performance is mediocre at best. Canada lacks a system-wide healthcare strategy that brings together the many individual federal/provincial/territorial strategies into a comprehensive and coherent whole. Managing a Canadian Healthcare Strategy is a collection of ten original policy research papers by leading Canadian and international scholars. It addresses three important questions. First, if Canada had a unifying strategy, how would we measure its success and monitor its performance? In this section, the role of big data and managerial quality metrics are explored. Second, who are the agents of change to bring about a Canadian system-wide strategy? By default, only governments are seen to be capable of effectively driving reform in healthcare. In this section, it is demonstrated that important agents of positive change must include health professions, patients, public and business. Third, how can the jurisdictional realities of Canada's political system be managed to bring about strategic reform? Although, barriers and impediments preoccupy Canadians, the final section explores some ways to overcome the challenges."--